2013
DOI: 10.3382/ps.2013-03075
|View full text |Cite
|
Sign up to set email alerts
|

Japanese quail meat quality: Characteristics, heritabilities, and genetic correlations with some slaughter traits

Abstract: The aim of this study was to evaluate the genetic parameters of several breast meat quality traits and their genetic relationships with some slaughter traits [BW, breast yield (BRY), and abdominal fat yield (AFY)]. In total, 1,093 pedigreed quail were slaughtered at 35 d of age to measure BRY, AFY, and breast meat quality traits [ultimate pH (pHU), Commission Internationale d'Eclairage color parameters (L*, lightness; a*, redness; and b*, yellowness), thawing and cooking loss (TL and CL, respectively), and War… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
46
3
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 44 publications
6
46
3
1
Order By: Relevance
“…However, contradictory data regarding pH exist. Narinc et al (2013) and Genchev et al (2008) reported higher pH values (5.94 and 6.17, respectively). Genchev et al (2008) suggest that the main reason behind the high pH values found in quail breast muscle were due to the morphology of muscle, which is mostly composed by aerobic-red muscle fibers.…”
Section: Performance and Carcass Traitsmentioning
confidence: 91%
“…However, contradictory data regarding pH exist. Narinc et al (2013) and Genchev et al (2008) reported higher pH values (5.94 and 6.17, respectively). Genchev et al (2008) suggest that the main reason behind the high pH values found in quail breast muscle were due to the morphology of muscle, which is mostly composed by aerobic-red muscle fibers.…”
Section: Performance and Carcass Traitsmentioning
confidence: 91%
“…Genetic parameters for early egg production and some reproductive traits were estimated by Strong et al (1978) and Mielenz et al (2006). only a few studies have presented the genetic parameters for feed efficiency, growth curve parameters, and meat quality traits in Japanese quail (Akbas and Yaylak, 2000;Aggrey et al, 2003;Aksit et al, 2003;Narinc et al, 2010a;Narinc et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The quail is used as an animal growth model for the muscle development because of its rapid generation time (Choi et al, 2014a, b), and also is a good source for meat products, especially in the Asian market, even though quail egg is more popular compared to meat (Narinc et al, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…There are many studies investigating how genetic selection influences muscle fiber and meat quality characteristics in chicken and turkey (Fowler et al, 1980; Cherel et al, 1994; Remignon et al, 1995; Velleman et al, 2002; 2003). However, there are only a few studies conducted on meat quality characteristics between the Japanese quail lines, even though there are many reports regarding the effects of genetic selection on ultimate muscle mass and fiber characteristics (Narinc et al, 2013; Choi et al, 2014a; Shin et al, 2015). Therefore, the objective of this study was to compare the characteristics of the pectoralis major muscle, muscle fiber, and meat quality characteristics between the HW and RBC quail lines to better understand the effects of selection for production efficiency of quail.…”
Section: Introductionmentioning
confidence: 99%